Pelatihan Berpikir Optimis untuk Meningkatkan Orientasi Masa Depan Remaja Tuna Daksa - Dewi Kamaratih Lisnawati; Ruhaena Juliani; Prasetyaningrum Prasetyaningrum (Universitas Islam Indonesia, 2016)
The purpose of this research was toempiricallyexamine the effect of optimism thinking training to increase future orientation of adolescence with disability. Respondents of this research was 16 teenagers who follow the pravocational program in YPAC Surakarta. Respondents divided into two groups: the experimental group consist of 8 person within treatment and the control group consist of 8 person without treatment. The method in this research was experimental pretest - posttest control group design with random assignment. The material which presented in the optimism thinking training was optimism, internal dialogue, the ABC model, explanatory style, disputation, and energizer. The results of data analysis showed that the optimism thinking training was significantly increase the future orientation of adolescence with disability. Except reconstructing cognitive skill, the respondents of this research also able to made the future design more detailed and realistic which appropriate with their self-capacity.Â Keywords : Optimism Thinking, Future Orientation, Disability